Relationship between ischemia-modified albumin and abdominal aortic calcification in maintenance hemodialytic patients - Yu Lan; Xu Xiao-hui; Wang Ying; Yao Ying; Liu Liu (Linchuang shenzangbing zazhi)
Objective To explore the level of ischemia-modified albumin（IMA）in patients with maintenance hemodialysis（MHD）and examine the association between IMA and abdominal aortic calcification（AAC）.Methods An observational study was conducted for 97 hemodialytic patients.Clinical data and laboratory parameters were recorded.Serum IMA was measured by a colorimetric assay based upon albumin-cobalt binding.And AAC was evaluated by a lateral lumbar spinal radiograph.According to the degree of calcification,they were divided into the groups of non-calcification（n=19）,mild calcification（n=26）,moderate calcification（n=37）and severe calcification（n=15）.IMA levels were compared in each group.Results The serum level of IMA for MHD patients was 83.82（74.30,97.44）U/mL.IMA level was positively correlated with dialytic duration（r=0.527,P<0.01）,calcium & phosphorus product（r=0.209,P<0.05）,serum iron（r=0.245,P<0.05）and AAC score（r=0.649,P<0.01）.IMA levels were 72.04（64.12,76.39）U/mL,82.03（71.96,88.47）U/mL,88.21（81.29,97.36）U/mL and 104.07（101.43,125.20）U/mL in non-calcification,mild calcification,moderate calcification and severe calcification groups respectively.Statistically significant differences existed among the groups（P<0.01）.With a threshold value of 76.95 U/mL,IMA provided a sensitivity of 75.6% and a specificity of 89.5% for predicting AAC.Conclusions Hemodialytic patients with AAC have an elevated level of IMA and it is correlated with the severity of calcification and the serum level of iron.IMA is an effective predictor of AAC in hemodialytic patients.